2015
DOI: 10.18632/oncotarget.6475
|View full text |Cite
|
Sign up to set email alerts
|

GPER is involved in the stimulatory effects of aldosterone in breast cancer cells and breast tumor-derived endothelial cells

Abstract: Aldosterone induces relevant effects binding to the mineralcorticoid receptor (MR), which acts as a ligand-gated transcription factor. Alternate mechanisms can mediate the action of aldosterone such as the activation of epidermal growth factor receptor (EGFR), MAPK/ERK, transcription factors and ion channels. The G-protein estrogen receptor (GPER) has been involved in the stimulatory effects of estrogenic signalling in breast cancer. GPER has been also shown to contribute to certain responses to aldosterone, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 80 publications
1
56
0
Order By: Relevance
“…Interestingly, the copper-chelating agent TEPA exerted an inhibitory action on the activation of the aforementioned pathway (90), in accordance with previous studies demonstrating that copper-chelating agents can exert anti-tumor effects (91). Altogether, these results indicate that diverse stimuli including hypoxia may trigger relevant biological responses through GPER, which was recently shown to be also involved in the stimulatory effects exerted by aldosterone in breast cancer cells and breast tumor-derived endothelial cells (92) as well as in pregnancy-induced vasodilation of rat uterine arteries (93).…”
Section: Gper Is Involved In Hypoxia-mediated Signalingsupporting
confidence: 89%
“…Interestingly, the copper-chelating agent TEPA exerted an inhibitory action on the activation of the aforementioned pathway (90), in accordance with previous studies demonstrating that copper-chelating agents can exert anti-tumor effects (91). Altogether, these results indicate that diverse stimuli including hypoxia may trigger relevant biological responses through GPER, which was recently shown to be also involved in the stimulatory effects exerted by aldosterone in breast cancer cells and breast tumor-derived endothelial cells (92) as well as in pregnancy-induced vasodilation of rat uterine arteries (93).…”
Section: Gper Is Involved In Hypoxia-mediated Signalingsupporting
confidence: 89%
“…10 nM) in the above-mentioned studies, binding has not been definitively demonstrated (Cheng et al 2014, Rigiracciolo et al 2016. Alternative mechanisms of aldosterone action via GPER may include direct physical association between MR and GPER (Rigiracciolo et al 2016), cross-talk via second messengers, GPER induction of local aldosterone synthase, and modification of the structural protein striatin, which can modulate steroid receptor function (Barton & Meyer 2015). However, the persistence of aldosterone responses in tissues lacking or deficient in MR and blocked by GPER antagonist is not explained by these alternative hypotheses (Feldman & Limbird 2015).…”
Section: Insulin-like Growth Factor-1 Receptor (Igf1r)mentioning
confidence: 86%
“…Here, the transactivation of PDGFR by MR facilitates translocation of c-Src to cholesterol-rich domains and its phosphorylation (Callera et al 2011b). Another potential R38 Review g s y ong and m j young Mineralocorticoid cell signalling 58 1 : R38 Review link is the G-protein coupled oestrogen receptor (GPER), which is required for MR-EGFR transactivation at least in one ER-negative breast cancer cell line (Rigiracciolo et al 2016). Furthermore, there is a synergistic relationship between MR and the EGFR.…”
Section: Interaction With Other Hormone Receptor Systemsmentioning
confidence: 99%
“…In addition, aldosterone induced cell proliferation and migration of tumor cells via GPER1, and it also induced pulmonary tumor spread that could be inhibited by spironolactone and GPER1 inhibition (Feldman et al 2016). Functionally, MR and GPER1 contribute to proliferation and migration of breast and endothelial cancer cells by mediating an upregulation of NHE1 (Rigiracciolo et al 2016). Consequently, there are many indications for functional involvement of GPER1 in rapid aldosterone/MR signaling (Ashton et al 2015) (Fig.…”
Section: Gper1mentioning
confidence: 99%